Pembelajaran Akidah Akhlak Berbasis Sains di Madrasah Ibtidaiyah Sentra Cendekia Muslim Balikpapan - Liya Utari (Journal on Education, 2024)
The harmonic strategy of integrating scientific concepts with ethics education guarantees that learning is not only efficient and effective but also meaningful. Using a saintifics method, students are encouraged to actively investigate and comprehend many ideas from a comprehensive standpoint, fostering their independence, feeling of accountability, creativity, and ability to observe. By combining the lesson's themes into a cohesive whole, the learning process facilitated by this approach enables students to apply the knowledge they have learned to their everyday work. This study used field research as its methodology, combining descriptive approaches with a qualitative approach. Analyzing the design, execution, and assessment of science-based ethics education is the aim of this study. The investigation's findings demonstrate: 1) The creation of an Islamic topics curriculum at Madrasah Centre of Muslim Scholars Balikpapan entails offering a range of curricula, including timetables for the entire year, semester, and academic year. 2) Teacher direction, discussion, and material application are all part of the moral education process. First-graders through sixth-graders study Asmaul Husna as their first subject. The Husna philosophy is put into practice through practical exercises, reading and conversation, and 3) In asynchronous and moral learning, the teacher evaluates each student's learning progress as well as their learning accomplishments through the evaluation of the semester test.